AMERICAN- ISRAELI RELATIONS DURING PRESIDENT BILL CLINTON'S REIGN - Mohammad Ali Al-Rousan (European Scientific Journal, ESJ, 2013)
The study aimed at investigating the qualitative change of American-Israeli relations during President Bill Clinton’s reign to recognize the American political policy and their practical applications concerning Israel to open channels of security and economic co-operation with Arab parties and guarantee Israeli superiority in the Middle East in general. Therefore, the study investigated the historical cultural background supporting those policies, the role played by the Zionist Lobby as a part of the secret government and the non-governmental pressure powers in the formation of the American bias to Israel. This was manifested in Clinton’s pressure on the Arab sides during the peace process courses for the accomplishment of the agreements and arrangements which could achieve the Israeli economic and security insertion in its Arabic Surrounding. The study concluded that Clinton's administration was the most biased to Israel resulting in creating new facts that make Israel the only winning side.